The The Impact of Fiscal Decentralization on SME activity in Kazakhstan: Regional Level Analysis - Amangeldi, Bibizhamal; Yedgenov, Bauyrzhan; Tolybay, Bekzhan (BUKETOV BUSINESS REVIEW, 2026)
This paper examines the impact of Kazakhstan’s 2020 corporate income tax (CIT) reform, which reassigned SME CIT revenues to regional budgets, on SME development from 2017–2023. Using regional panel data with fixed effects, results show that the reform significantly increased SME registration, employment, output, and gross value added. The effects were strongest for small firms and individual entrepreneurs, reflecting enhanced local fiscal incentives. The findings suggest that fiscal decentralization can stimulate regional entrepreneurship and economic activity by strengthening local governments’ capacity and motivation to support SMEs. Policy implications highlight the importance of sustained subnational fiscal autonomy for inclusive growth.